Computer-Based Employment Applications: Implications for Offenders and Supervising Officers. - Kelly, Christopher E.; Fader, Jamie J. (Federal Probation, 2012)
The article presents the effects of computer-based employment applications to offenders and supervising officers. Among the results revealed in the study include the difficulty it poses to returning prisoners due to less access to computers, and level of computer proficiency. The authors noted the need to help the prisoners be prepared in taking online application and testing.